Positive Perception of Dental Medicine Students on Dental Aesthetics Based on the Semester Being Pursued - Nathania, Rania Vivian; Fanny, Geo; Luthfimaidah, Mahela Sefrian; Leksono, Paquita Maharani; Brilyanti, Yasmin Tasya; Fardha, Dimas Rudianto; Dewi, Rosalyn Surya; Kusumo, Aryo Dwipo (International Journal of Psychosocial Rehabilitation, 2020)
Background: Aesthetics is a concept referring to beauty. Nowadays, media often perpetuates the concept of beauty by showing faces with attractive looks and high aesthetic value. The appearance of teeth is one aspect determining the attractiveness of someone’s face and playing an important role in social interaction. Variations in aesthetic standards lead to different perceptions about the aesthetics of the teeth between one person and another. Objective: This study was conducted with an aim for obtaining value from the self-perception of students of the Faculty of Dental Medicine at Universitas Airlangga regarding their satisfaction with their dental aesthetics and its correlation with their level of education. Methods: The study used a descriptive study method towards the student of the Faculty of Dental Medicine at Universitas Airlangga from the first, third, and fifth semester. Results of the Study: More than half of the total respondents had good perceptions of their dental aesthetics. The lowest percentage of respondents who had positive perceptions in this study was from the first semester because only 55.89% were satisfied with their dental aesthetics. Meanwhile, students from the third semester occupied the highest percentage of respondents who had positive perceptions (73.5%). Conclusion: Positive perceptions of Universitas Airlangga Faculty of Dental Medicine students increased from the first until the third semester, and decreased in the third until the fifth semester.